2018
DOI: 10.5114/jcb.2018.74137
|View full text |Cite
|
Sign up to set email alerts
|

Should molecular subtype be recommended as one of the selection criteria for accelerated partial breast irradiation? Preliminary results from an Asian cohort

Abstract: PurposeThe purpose of this study was to report clinical outcomes in patients treated with accelerated partial breast irradiation (APBI), stratified as per molecular subtype and American Society for Therapeutic Radiology and Oncology/Groupe Européen de Curiethérapie and European Society for Radiotherapy & Oncology (ASTRO/GEC-ESTRO) patient selection criteria in order to determine whether molecular subtype should be recommended as one of the selection criteria for APBI.Material and methods157 early-stage breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It should be noted that for breast cancer patients >50 years of age undergoing APBI, HER2-enriched subtype has a significantly higher risk of 5 years IBTR and 5 years regional nodal recurrence (RNR) than that in all other subtypes, whereas luminal A subtype has the lowest risk of all subtypes 45. A similar conclusion was reached in some clinical trials following multi-catheter APBI (mAPBI)42 and single-entry catheter APBI (sAPBI) 46. In the mAPBI trial, HER2-positive status was associated with the shortened DM-free survival, DFS, and OS and the 5 years IBTR of HER2-enriched breast tumors and 5 years RNR of TNBC were significantly higher than those in luminal A disease in the sAPBI trial (Table 2).…”
Section: The Comparison Of Prognosis Between Four Subtypes Under Varimentioning
confidence: 60%
See 1 more Smart Citation
“…It should be noted that for breast cancer patients >50 years of age undergoing APBI, HER2-enriched subtype has a significantly higher risk of 5 years IBTR and 5 years regional nodal recurrence (RNR) than that in all other subtypes, whereas luminal A subtype has the lowest risk of all subtypes 45. A similar conclusion was reached in some clinical trials following multi-catheter APBI (mAPBI)42 and single-entry catheter APBI (sAPBI) 46. In the mAPBI trial, HER2-positive status was associated with the shortened DM-free survival, DFS, and OS and the 5 years IBTR of HER2-enriched breast tumors and 5 years RNR of TNBC were significantly higher than those in luminal A disease in the sAPBI trial (Table 2).…”
Section: The Comparison Of Prognosis Between Four Subtypes Under Varimentioning
confidence: 60%
“…Recently, the correlations of molecular subtypes with the prognosis of breast cancer patients who were treated with APBI have been extensively investigated. In the study of Wadasadawala et al, who evaluated the treatment outcomes of ESBC patients after receiving APBI,42 it was shown that the 3 years LR and LRR across different molecular subtypes were not significantly different whereas the 3 years DM-free survival, OS, and disease-free survival (DFS) of HER2-positive subtype were significantly lower than those of luminal A and B phenotypes. Moreover, in 2016, Dr. Wilkinson introduced a 5-year follow-up clinical results of APBI treatment in 278 ESBC patients,43 which indicated no significant difference in the incidence rates of IBTR, DM, DFS, and OS between four phenotypes of breast tumors (Table 2).…”
Section: The Comparison Of Prognosis Between Four Subtypes Under Varimentioning
confidence: 99%
“…After layers of screening, which was shown in Figure 1, we finally obtained 4 articles [1215] with 1740 women for clinical outcomes analysis, 7 trials [1622] with 1255 people for acute RT-related toxicity analysis as well as 10 studies [1625] with a total of 1565 patients for late RT-related toxicity analysis. Of the patients who were reported the association between molecular subtypes and clinical outcomes, 1166 (84.2%) had Luminal A/B breast cancer, 154 (11.1%) were classified into TN disease, 64 (4.6%) suffered from HER2-enriched breast tumor.…”
Section: Resultsmentioning
confidence: 99%
“…Patient selection for APBI is an evolving field, with regular updates made to the consensus guidelines as recently as 2017 [13]. However, prior studies have been unable to demonstrate the ability for these guidelines to significantly predict IBTR [11, 16–21]. Budrukkar et al investigated the utility of the current guidelines in a retrospective study of 240 women treated with multicatheter interstitial brachytherapy APBI [20].…”
Section: Discussionmentioning
confidence: 99%